Value Chain and Techno-Economic Analysis of Biodiesel Production from Rubber Seeds in Banyuasin, Indonesia - Adela Damika Putri; Muhamad Aldi Nurdiansyah; Lili Melani; Angga Dwiartama; Muhammad Yusuf Abduh (School of Life Sciences and Technology, Institut Teknologi Bandung, 2026)
Banyuasin Regency, located in the province of South Sumatra, has the largest area of rubber plantations in Indonesia, with huge potential as biodiesel feedstock, and generates income for rubber planters through the exploitation of the seeds. This study focuses on the value chain of the exploitation of seeds for biodiesel and its economic benefits to the planters using the Hayami method. The snowball and stratified random sampling methods were used to determine the pricing of the seeds. The value chain actors include the rubber planters, the crumb rubber processing and marketing unit, the biodiesel processing unit, and the consumers, which operate through the market governance structure. The findings indicate that rubber seed processing generates an added value of IDR 4,937/kg, with a value-added ratio of 64%, classifying it as a high-value commodity. Furthermore, integrating rubber seed value chain activities has the potential to increase farmers’ annual income by IDR 3,850,000, contributing to financial sustainability. A techno-economic analysis confirms the feasibility of intermediate-scale biodiesel production in Banyuasin Regency, with a benefit-cost ratio of 1.35, demonstrating its potential to create substantial economic value from rubber seeds. These findings highlight a strategic opportunity for the crumb rubber processing and marketing unit in the Banyuasin Regency to enhance its role within the supply chain while improving farmer profitability. By optimizing value chain efficiency and ensuring market stability, rubber seed-based biodiesel production can contribute to economic growth, rural development, and renewable energy advancement in Indonesia.